Positive and Neutral Needleless Connectors: A Comparative Study of Central-line Associated Bloodstream Infection, Occlusion, and Bacterial Contamination of the Connector Lumen. Issue 3 (May 2023) - Schora, Donna; Patel, Parul; Barza, Ruby; Patel, Jignesh; Wilson, Kathleen; Espina-Gabriel, Paulette; Nunez, Vesna; Singh, Kamaljit
Abstract : A pragmatic, multiphase prospective quality improvement initiative was performed to determine whether a positive displacement connector (PD) causes reduction of central line-associated bloodstream infection (CLABSI), occlusion, and catheter hub colonization when compared with a neutral displacement connector with alcohol disinfecting cap (AC). Patients with an active central vascular access device (CVAD) were enrolled March 2018 to February 2019 (P2) and compared to the prior year (P1). Two hospitals were randomized to use PD without AC (Hospital A) and with AC (Hospital B). Two hospitals utilized a neutral displacement connector with AC (Hospitals C and D). CVADs were monitored for CLABSI, occlusion, and bacterial contamination during P2. Of the 2454 lines in the study, 1049 were cultured. CLABSI decreased in all groups between P1 and P2: Hospital A, 13 (1.1%) to 2 (0.2%); Hospital B, 2 (0.3%) to 0; and Hospitals C and D, 5 (0.5%) to 1 (0.1%). CLABSI reduction was equivalent between P1 and P2 with and without AC, at around 86%. The rate of occlusion per lumen was 14.4%, 12.1%, and 8.5% for Hospitals A, B and C, D, respectively. Hospitals using PD had a higher rate of occlusion than those that did not ( P = .003). Lumen contamination with pathogens was 1.5% for Hospitals A and B and 2.1% for Hospitals C and D ( P = .38). The rate of CLABSI was reduced with both connectors, and PD reduced infections with and without the use of AC. Both connector types had low-level catheter hub colonization with significant bacteria. The lowest rates of occlusion were found in the group using neutral displacement connectors.